Small Arms and Light Weapons Proliferation and Gun Violence in West Africa Sub-Region - Agbegbedia Oghenevwoke Anthony (International Studies Journal)
The unlawful use of small arms, light weapons proliferation and gun violence is a global problem which affects every country. At the global stage, it is well known that far more people are killed in armed conflict through the use of small arms than by bombs. The study therefore examined the sources and modes of transfer of these weapons and their effects on the citizenry. Data were sourced using both primary and secondary methods. Data selected was analysed through the use of descriptive method such as tables and frequency distribution. Findings revealed that the porous borders across the West African sub region is one of the causes of small arms, light weapons proliferation and gun violence and this has led to destruction of lives and properties. The government of the countries in the West African sub region should collaborate to beef securities in their borders.